(3JegjO GdbhGYOs - (3GdYGedj, GHf GdMGLI, Rjf GdOjf Hf Ydj Hf CMeO, J (B966(3g`s ((3eMeO TajY Hf YHO GdhGMO ajQhRBHGOjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj habfG dJegjO bhGYO GdCMcGe GdTQYjI(B... (3hHYO aEf Yde Gdabg dG jNai TQag haVdgs
(3BNQgG (B:s
(3ddaQb Hjf GdcdeI HGdVGO hGdXGA adGHO ef GdEJjGf HGdeWdhH TQYG aj GdaGJMI(B. (3fSCd Gddg MSf GdNGJeI(B...s
(3JHUQI GdeDda (B:s
(3GdTgjO GdKGfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B3(3, U(B64s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B741s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis